Efficient ε-poly-L-lysine production by Streptomyces albulus based on a dynamic pH-regulation strategy. (July 2022) - Wang, Liang; Deng, Yue; Wu, Mengping; Zhang, Jianhua; Zhang, Hongjian; Mao, Zhonggui; Chen, Xusheng
Abstract: Previous studies have demonstrated that the biosynthesis of ε-poly-L -lysine (ε-PL) is suppressed due to the decrease in cell viability in the late phase of fed-batch fermentation. To address this, a dynamic pH-regulation strategy was developed to maintain and improve ε-PL production. Using the method proposed here, ε-PL production and productivity reached 60.2 g/L and 7.5 g/L/d, respectively, both of which were 36.5% higher compared to the case for the fermentation without dynamic pH regulation. Changes in cell viability, key enzyme activity, respiratory chain activity and intracellular nucleotide levels were detected and analyzed. The results showed that increases in glucose consumption, L -lysine biosynthesis pathway activity, oxidative phosphorylation, and ATP levels are responsible for the improved ε-PL production by the dynamic pH-regulation strategy. Furthermore, the reactive oxygen species (ROS) levels and the activities of cellular antioxidant systems were enhanced, which are also important factors for the increased ε-PL biosynthesis capacity and cell viability. Overall, the dynamic pH-regulation strategy is a convenient and effective approach for promoting ε-PL biosynthesis by strengthening carbon and energy metabolism, ROS level and antioxidant capacity. Graphical Abstract: ga1 Highlights: A novel dynamic pH regulation strategy was developed. ε-PL (ε-poly-L -lysine) production was promoted from 44.1 to 60.2 g/L. Dynamic pH regulation strategy enhanced cell metabolism. Dynamic pH regulation strategy strengthened cellular antioxidant capacity. This work would contribute to industrial production of ε-PL.